Kesiapan Unit Pelaksana Teknis Praktik Pengalaman Lapangan (UPT PPL) Melakukan Manajemen Micro Teaching dan Praktik Pengalaman Lapangan (PPL) dalam Menyiapkan Guru Profesional - Melda Delvia (Departement of Mathematics Education, 2023)
The purpose of this research is to: describe and reveal the readiness of UPT PPL to manage micro teaching and Field Experience Practices (PPL) in preparing professional teachers at Private Islamic Religious Universities in Padang City. The type of research used is field research with a descriptive qualitative approach. The results showed that: In Private Islamic Religious Universities (PTAIS) in Padang City, which prepares micro teaching management and Field Experience Practices (PPL) is not the Technical Implementation Unit of the Field Experience Program (UPT PPL), but the management of micro teaching and Field Experience Practices (PPL) is separate. Micro teaching is carried out like an ordinary course, its management is under the responsibility of the chairman / dean. While the Field Experience Practices (PPL), the management is managed by the Field Experience Practices (PPL) committee which is selected every time the Field Experience Practices (PPL) will be carried out under the responsibility of the chairman/dean.